Outcome of union and infection in supracondylar fracture of femur treated with distal femur locking plate among adult patients from 2014 to 2018 - Jaffar, Nik Muhammad Shahid Nik (2020)
Introduction: Supracondylar fractures of femur is relatively uncommon and carries significant morbidity. Locked plate of distal femoral fractures are widely used for treatment recently. However, the literature reports on the outcome of treatment are variable. The purpose of our study is to study and analyze the union and infection rate of supracondylar fracture of femur treated with distal femur locking plate among adult patients in HSNZ and HUSM. Methodology: This was a retrospective cohort study involving 92 patients with supracondylar fracture of femur treated with distal femur locking plate evaluated from 2014 till Jun 2018 from two trauma centers. The clinical data and imaging were retrieved from patient’s record. Radiological union and infection were used as outcome variables. Demographic data, fracture classification (33A and 33C), fracture type (open and closed), associated injury that can alter rehabilitation, injury mechanism, diabetes and smoking status were regarded as associated factors. Result: Sixty eight (73.9%) of patients with supracondylar femur fractures achieved union while 24 (26.1%) developed non-union. Ten (10.9%) patients were diagnosed with infection. There was no significant association between fracture classification (either 33A or 33C) of fracture including both open and closed fractures with union and infection outcome. Diabetes (OR 1.35) was found to increase risk to get non-union but it is not statistically significant (p=0.60). For infection, diabetes (OR 8.9, p = 0.02), smoking (OR 10.84, p = 0.008) and patient with associated injury that alter rehabilitation program (OR 6.56, p = 0.04) are found to be significant. Conclusion: Our study showed that the union and infection rate in fracture distal femur type 33- A and 33-C are overall satisfactory. Being diabetic, smoking and associated injury that can alter rehabilitation are the associated factors that have a significant effect on infection.